Social media marketing research at the hotel industry in Slovakia - Palencarova, Martina (2022)
Social networks are the main marketing entity of the hotel industry of the 21st century. To understand the impact that social networks have on the hotel sector, both from the point of view of the hotel and the consumer is becoming essential. The aim of this research is to find out how 5 stars Slovakian hotels present themselves in 3 different social networks Instagram, Facebook and Twitter and to compare them with each other. For that purpose a descriptive analyses of the most relevant features of this social networks was conducted. The study offers relevant insight for marketing practitioners in the hospitality industry